A massive experiment on choice blindness in political decisions: Confidence, confabulation, and unconscious detection of self-deception - Rieznik, Andrés Anibal (2017)
We implemented a Choice Blindness Paradigm containing political statements in Argentina to reveal the existence of categorical ranges of introspective reports, identified by confidence and agreement levels, separating easy from very hard to manipulate decisions. CBP was implemented in both live and web-based forms. Importantly, and contrary to what was observed in Sweden, we did not observe changes in voting intentions. Also, confidence levels in the manipulated replies where significantly lower than in non-manipulated cases even in undetected manipulations. We name this phenomenon unconscious detection of selfdeception. Results also show that females are more difficult to manipulate than men.